Modified Rijndael Algorithm for Resource-Constrained IoT-Based Wireless Sensor Networks: IoT-Based Wireless Sensor Networks - Sirajuddin, Mohammad; Kumar, Dr. B. Sateesh (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: IoT devices are small, have limited battery and computing capabilities, and cannot tolerate complex encryption. OBJECTIVES: Many encryption algorithms struggle to strike a balance between security and complexity. Increasing the level of security necessitates increasing complexity, which leads to higher encryption and decryption times. This research aims to provide a novel encryption method, Modified Rijndael Algorithm that balances security and complexity. METHODS: The classic Rijndael encryption technique has been modified to make it lighter and more secure, suitable for resource-constrained IoT devices. RESULTS: These modifications include adding the novel pre-processing step SISA-Crossover based on the two-point crossover operation of genetic algorithms, removing the Sub Byte step, changing the shift column phase, and decreasing the rounds. CONCLUSION: The proposed technique provides speed and higher security in encryption and decryption, increasing efficiency and randomness while reducing encryption and decryption times by 21.06% and CPU consumption by 13.2% compared to the traditional method.
Keywords: modified rijndael algorithm; lightweight cryptography; IoT security; MRA